THE STUDY OF EDUCATION QUALITY ASSURANCE SYSTEM TO IMPROVE THE QUALITY OF PRIMARY SCHOOLS AT SD N 2 BENDOSARI BOYOLALI - Santri Prabowo Utomo; Sri Marmoah; Roemintoyo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
If a system is arranged and implemented clearly, correctly, systematically, and reported responsibly, it will simplify the users’ task. Therefore, the quality assurance system of education in primary schools is very important in accordance with existing procedures to maintain and advance the quality of education of a school. There needs to be an efficient, effective, and appropriate way to assure the quality of education in a school, namely primary schools. This study aims to describe the results of the analysis of the education quality assurance system at Bendosari SD N 2 (State Primary School 2), Sawit, Boyolali. The approach used in this research was a descriptive qualitative approach with case study design. This data collection technique was in the form of the results of observation activities, interview activities, questionnaire filling activities, and documentation activities. Sources of data in this study came from school residents such as: school committees, principals, teachers, students, parents of students, communities, and researchers. Data validity techniques to find the validity and validity of the data used data triangulation. Data analysis techniques used in this study were interactive qualitative data analysis by Miles and Huberman (2014) consisting of data reduction (summarizing data), data presentation (displaying data), and drawing conclusions from research. The results obtained in this study were to describe and explain that the quality assurance of education conducted by SD N 2 Bendosari, Sawit, Boyolali can be maintained properly and to improve the education quality assurance system in order to achieve a goal.